Laboratory Characterization and Influence of Mineralogy and Grading on the Performance of Treated and Untreated Granular Materials Used as Surface Pavements in Unpaved Road - L. Beaulieu; P. Pierre; J.-P. Bilodeau (Advances in Civil Engineering)
This paper presents the results of a laboratory study on the influence of grading and granular mineralogy sources (granitic gneiss, basalt and limestone) on the performance of treated and untreated granular materials used as surface pavements in unpaved roads. Results of bearing capacity, resilient modulus and compressive strength tests are discussed. Natural brine, calcium chloride, cement and a polymer emulsion treated samples were tested and compared to untreated samples. The combinations of product, mineralogy and grading showing great performance are finally pointed out.